1980
DOI: 10.1007/bf00232136
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of atrial endocardium and myocardium in three species of Gadidae (Teleostei)

Abstract: The atrial endocardium and myocardium in three teleost species Gadiculus thori J. Smith, Melanogrammus aeglefinus (L.) and Onos cimbrius L. of the family Gadidae are described. The myocardial cells contain few myofibrils and a moderately developed sarcoplasmic reticulum and are connected by short nexuses. G. thori has many atrial specific granules in some of the myocardial cells facing the endocardium. Such cells contain little contractile material. The endocardium is composed of tall cells (10 micrometer) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…Most MDBs are filled with homogeneous material and are thought to be the storage site for glycosaminoglycans (GAGs) [Benjamin et al, 1984;Greer Walker et al, 1985]. However, the similarity in morphology and in the number and distribution of MDBs is not complete across species [see Leknes, 1981a;Benjamin et al, 1984;Icardo et al, 1999a, b], and contents other than GAGs have been suggested [Saetersdal et al, 1974;Leknes, 1980Leknes, , 1981bDoi et al, 1995]. The existence in the eel of MDBs that show different types of contents suggests that MDBs store different types of molecules with different functional roles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most MDBs are filled with homogeneous material and are thought to be the storage site for glycosaminoglycans (GAGs) [Benjamin et al, 1984;Greer Walker et al, 1985]. However, the similarity in morphology and in the number and distribution of MDBs is not complete across species [see Leknes, 1981a;Benjamin et al, 1984;Icardo et al, 1999a, b], and contents other than GAGs have been suggested [Saetersdal et al, 1974;Leknes, 1980Leknes, , 1981bDoi et al, 1995]. The existence in the eel of MDBs that show different types of contents suggests that MDBs store different types of molecules with different functional roles.…”
Section: Discussionmentioning
confidence: 99%
“…The endocardium of the eel bulbus arteriosus is formed by flattened cells containing numerous membrane-bound vacuoles that can be identified as moderately dense bodies (MDB) [see Leknes, 1980;Benjamin et al, 1983;Icardo et al, 1999a, b]. MDBs have been demonstrated in the endothelial cells of the bulbus arteriosus in most teleosts studied to date.…”
Section: Discussionmentioning
confidence: 99%
“…The heart endocardial layer covering the cardiac muscle trabeculae is 'specialized' in some bony fish families, and 'unspecialized' in others (Leknes 1980(Leknes , 1983. Recent studies have revealed that the specialized endocardium in teleosts is able to take up large amounts of various foreign organic macromolecules from the blood stream (Leknes 1987, Smedsrød et al 1995, Dalmo et al 1996, Sørensen et al 1998, Leknes 2001a.…”
mentioning
confidence: 99%
“…Two-thirds of the water was changed each month with clean tap water (pH 6-7). Three days after the last feeding, they were euthanized with an overdose of a 0.5 % chlorobutanol solution, and oesophagus and stomach were fixed at 4°C for a week in formaldehyde prepared 24 h before the use by dissolving 4 g of paraformaldehyde in 96 ml phosphate buffer solution (pH 7.4) at 90°C (Grimstone and Skaer 1972;Leknes 1980); alternatively, fixation was done in a modified alcoholic fixative resembling that described by Reite (1996), composed of 100 % ethanol, 37 % formaldehyde, and 100 % acetic acid in a volume ratio 85:10:5. After cleansing in buffer or ethanol solution depending on the fixative, the tissues were dehydrated in ethanol, treated with xylene, embedded in paraffin wax, and sectioned.…”
Section: Methodsmentioning
confidence: 99%